National identity: research approaches - N. V. Saraeva; G. R. Pachin; N. N. Pachina; T. A. Shchebzukhova (Современная наука и инновации, 2024)
The problem of national identity requires its solution in a situation of collision and mixing of different cultures and national traditions. National identity is determined by socio-cultural, historical, religious and other factors that form the unique image of the people, their customs, traditions, culture, language, and mentality. The study of national identity in a multinational state is relevant and in demand in modern reality. The purpose of the work is to identify approaches to the study of national identity. In this regard, the characteristic of the concept of ―identity‖ is given, the definition of the category ―nation‖ is stated, the conceptual field of national identity is investigated, the political and legal approach to the study of national identity is described, and the cultural and linguistic approach to the study of national identity is characterized. The formation of national identity is the central problem of a multinational state. It is important to define approaches to the study of this phenomenon. The article examines the political, legal, cultural and linguistic approaches to the definition of national identity, substantiates the central categories associated with the conceptual field of national identity, gives characteristics to the concepts of ―identity‖, ‖nation‖, ―national identity".